Impact of lenvatinib on renal function compared to sorafenib for unresectable hepatocellular carcinoma. Issue 19 (13th May 2022) - Sasaki, Ryu; Fukushima, Masanori; Haraguchi, Masafumi; Honda, Takuya; Miuma, Satoshi; Miyaaki, Hisamitsu; Nakao, Kazuhiko
Abstract : Abstract: Anti-VEGF drugs, such as tyrosine kinase inhibitors, play an important role in systemic therapy for unresectable hepatocellular carcinoma (uHCC). We examined the effects of sorafenib and lenvatinib on proteinuria and renal function. Patients who were administered sorafenib (n = 85) or lenvatinib (n = 52) as first line treatment for uHCC from July 2009 to October 2020, were enrolled in this retrospective observational study. A propensity score analysis including 13 baseline characteristics was performed. Eighty four patients were selected (sorafenib, n = 42; lenvatinib, n = 42) by propensity score matching (one-to-one nearest neighbor matching within a caliper of 0.2). We analyzed changes in estimated glomerular filtration rate (eGFR) during tyrosine kinase inhibitor treatment, as well as the development of proteinuria in both groups. A multivariate analysis was performed to identify predictors of a deterioration of eGFR. At 4, 8, 12, and 16 weeks, ΔeGFR was significantly lower in the lenvatinib group than in the sorafenib group ( P  < .05). The lenvatinib group showed a significantly higher frequency of proteinuria than the sorafenib group (30.9% vs 7.1%, P  = .005) and had a higher rate of decrease in eGFR than the sorafenib group ( P  < .05). Multivariate analysis revealed that lenvatinib use was the only predictive factor of eGFR deterioration (odds ratio 2.547 [95% CI 1.028–6.315], P  = .043). In cases of proteinuria ≤1+ during lenvatinib treatment, eGFR did not decrease. However, eGFR decreased in the long term (>24 weeks) in patients who have proteinuria ≥2+. Lenvatinib has a greater effect on proteinuria and renal function than sorafenib. In performing multi-molecular targeted agent sequential therapy for uHCC, proteinuria and renal function are important factors associated with drug selection after atezolizumab-bevacizumab combination therapy currently used as the first-line treatment.